2005
DOI: 10.1089/jop.2005.21.242
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Dorzolamide/Timolol Fixed Combination Versus Latanoprost in the Treatment of Ocular Hypertension or Glaucoma: Combined Analysis of Pooled Data from Two Large Randomized Observer and Patient-Masked Studies

Abstract: In previous analyses of primary efficacy data from two randomized clinical trials, standard dosing regimens of the dorzolamide/timolol fixed combination (COSOPT) and latanoprost (XALATAN) were shown to have equivalent efficacy with regard to reduction in mean daytime diurnal intraocular pressure (IOP). We performed additional post hoc analyses of pooled data from these studies to compare further the efficacy of the two treatments. The studies used identical 3-month, parallel group, randomized, observer-masked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 13 publications
1
1
1
Order By: Relevance
“…These findings are compatible with those reported by other authors who have shown equal efficacy of these 2 treatment regimens. [34][35][36] With respect to tolerability and safety, the profile and incidence of AEs observed in the present study were similar to those reported in randomized clinical trials, with local ocular reactions such as eye irritation and pain being the most common side effects followed by bitter taste. 24,33 As with other topical ophthalmic agents, systemic absorption of DT may occur and AEs associated with systemic administration of either active component may be expected.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These findings are compatible with those reported by other authors who have shown equal efficacy of these 2 treatment regimens. [34][35][36] With respect to tolerability and safety, the profile and incidence of AEs observed in the present study were similar to those reported in randomized clinical trials, with local ocular reactions such as eye irritation and pain being the most common side effects followed by bitter taste. 24,33 As with other topical ophthalmic agents, systemic absorption of DT may occur and AEs associated with systemic administration of either active component may be expected.…”
Section: Discussionsupporting
confidence: 84%
“…33 Fechtner et al reported a mean change of À7.5 mmHg at 3 months of treatment from an untreated baseline value of 25.7 mmHg in patients treated with DT. 34,35 The mean reduction in IOP reported in the present study is higher than that observed in these randomized clinical trials and this may be attributed to the selection of patient with elevated IOP or with more advanced disease. At the end of 12 weeks of treatment, the effectiveness of the fixed combination of DT was similar to that observed for the patients who required treatment with latanoprost between 6 and 12 weeks.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, in the staging of glaucoma, a variety of structural and functional testing methods are performed (18,20) . Many research groups have studied and compared the efficacy of CAI+β blocker fixed-dose combination therapy and PGAs inpatients with POAG (21)(22)(23)(24) . However, the IOP-lowering effects of these drugs may differ between PXG and POAG (4) , and only a few studies have compared PGA with CAI+β blocker fixed-dose combination therapy in PXG, none of which analyzed the influence of glaucoma stage on the IOP-lowering effect (25,26) .…”
Section: Introductionmentioning
confidence: 99%